Nutritional status and production of 'Pêra' sweet orange related to cover crops and mulch - Neto, Horst Bremer; Filho, Ricardo Victoria; Filho, Francisco de Assis Alves Mourão; Menezes, Gilberto Mendonça de; Canali, Émerson (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effects of cover crops composed of grass and perennial leguminous in the orchard inter-rows and mulch on the rows, on soil chemical characteristics and nutritional status of Citrus sinensis (L.) Osbeck cv. Pêra sweet orange budded on 'Rangpur' lime (Citrus limonia Osbeck). The treatments were: T1, Cover crop of Brachiaria ruziziensis R. Germ. & Evrard, without mulch on the row; T2, B. ruziziensis and mulch on the row; T3, B. ruziziensis and Arachis pintoi and mulch on the row; T4, B. ruziziensis and stylosanthes and mulch on the row; T5, Brachiaria plantaginea and mulch on the row; T6, Arachis pintoi and mulch on the row; T7, stylosanthes and mulch on the row. Stylosanthes increased N leaf content compared to B. ruziziensis. Grass mulch had no significant effect on N leaf content. There was significant interaction between root density into superficial soil layer, P leaf content and yield.